Rapid and precise large area mapping of rare-earth doping homogeneity in luminescent materials - Jan Hrabovsky; Miroslav Kucera; Lucie Palousova; Jakub Zazvorka; Jan Kubat; Lei Bi; Martin Veis (Communications Materials)
Abstract Doping of luminescent materials by rare-earth ions is common practice to achieve desired emission properties for a large variety of applications. As several rare-earths ions are frequently combined, it is subsequently difficult to effectively detect and control their homogeneous distribution within the host material. Here, we present a simple, rapid, large scale and precise method of rare-earth mapping using a commercial UV-Vis scanner. We discuss the influence of rare-earth distribution on the physical, optical and luminescent properties with no observable qualitative effect on photoluminescent properties and optical anisotropy. On the contrary, rare-earth-rich areas exhibit significantly higher values of refractive index and optical absorption, which allowed for their identification by the commercial scanner device. The presented method thus provides fast and accurate information about the rare-earth distribution in the material volume with high resolution (≈2.7 µm) and low limit of concentration difference detection (≈0.014 at.%) compared to other techniques, which makes it a promising candidate for high throughput measurements.